THE EXPERIENCE OF HEALTHCARE WORKERS AND PATIENTS IN THE IMPLEMENTATION OF DISCHARGE PLANNING FOR HEART FAILURE PATIENTS - Sanusi, Amoy Amelia; Dewi, Wan Nishfa; Bayhakki, Bayhakki; Wahyuni, Sri; Huda, Nurul; Erika, Erika (Poltekkes Kemenkes Jakarta III, 2025)
Ineffective discharge planning results in discontinuity of patient care at home. This condition worsens patient outcomes, leading to patients returning to health services with the same medical history or with new and more severe complications. This study aims to explore the experience of healthcare workers and patients in implementing discharge planning for heart failure patients. This study employed a phenomenological design with a qualitative, interpretative approach. The participants consisted of 17 individuals: ten health workers from a private hospital in Pekanbaru, two heart specialists, three nurses, two pharmacists, three nutritionists, and seven patients with heart failure who were planning to return home. Participant recruitment was conducted using a purposive sampling method. Data collection was through in-depth interviews, and data analysis used the Colaizzi analysis stages. Four themes are interrelated with the studied phenomena: the information received by patients regarding discharge planning, specific education for heart failure patients, the challenges faced by healthcare workers in completing the discharge planning form, and the important components of discharge planning for heart failure patients. The experiences of healthcare workers and patients in implementing discharge planning in this study reveal that there are still inadequacies that concern both healthcare workers and patients. The themes identified in this study can contribute to the development of discharge planning forms for heart failure patients. Therefore, this study on healthcare services suggests that it may reduce the recurrence rate of heart failure in patients.